2013
DOI: 10.1111/jmp.12044
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between serum levels of beta amyloid, cerebrospinal levels of tau and phospho tau, and delayed response tasks in young and aged cynomolgus monkeys (Macaca fascicularis)

Abstract: Circulating Aβ42 levels were lower in Aged monkeys and were correlated with inferior performance on delayed response tasks in Aged animals; therefore, both measures may be useful in establishing cynomolgus monkeys as models for studies of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
(64 reference statements)
1
29
0
Order By: Relevance
“…Our studies of cynomolgus monkeys have identified an age-related decline in DRT performance (Darusman et al, 2013a). We also found that DRT performance was correlated with circulating levels of amyloid-beta (Aβ) levels (Aβ—specifically Aβ 42 ; Darusman et al, 2013b; Yue et al, 2014). Expanding our study, we found indications that structural magnetic resonance imaging could be used to identify abnormalities, such as atrophy in the hippocampus and cortical areas, in aged monkeys with poor memory and low circulating Aβ 42 levels (Darusman et al, 2014b).…”
Section: Introductionmentioning
confidence: 78%
“…Our studies of cynomolgus monkeys have identified an age-related decline in DRT performance (Darusman et al, 2013a). We also found that DRT performance was correlated with circulating levels of amyloid-beta (Aβ) levels (Aβ—specifically Aβ 42 ; Darusman et al, 2013b; Yue et al, 2014). Expanding our study, we found indications that structural magnetic resonance imaging could be used to identify abnormalities, such as atrophy in the hippocampus and cortical areas, in aged monkeys with poor memory and low circulating Aβ 42 levels (Darusman et al, 2014b).…”
Section: Introductionmentioning
confidence: 78%
“…From previous studies, we selected aged subjects above 20 years old that met the requirements of low levels of Aβ 42 (<5000 pg/ml) and low DRT performance (<40%) for the memory-affected group (Darusman et al, 2013a,b). Aged subjects characterized by high-circulating Aβ 42 and high DRT performance were selected for the age-matched control group.…”
Section: Methodsmentioning
confidence: 99%
“… Data are collected from the references Darusman et al (2013a,b). DRT performance is presented as the collected percent of trials where the subject could correctly retrieve a hidden item following a predetermined delay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations